IDENTIFICATION OF FINITE TYPE ALGEBRA - KASYFIL AZI (NIM : 10108065); Pembimbing : Dr. Muchtadi Intan Detiena, RYAN
A finite type algebra is an algebra which has finitely many indecomposable modules. In this work, we will identify the graphs which correspond to finite type algebras using Gabriel Theorem.